ASSESSMENT OF PECTINMETHYLESTERASE ACTIVITIES (PME) IN THE JUICE OF TROPICAL FRUITS PURCHASED FROM THE ROMANIAN MARKET - Vasilica SIMION; Ciprian Nicolae POPA; Radiana-Maria TAMBA-BEREHOIU; Rodica CULEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this paper was to evaluate comparatively pectinmethylesterase activities (PME) from the juice of some tropical fruits purchased from the Romanian market. In this respect, a series of parameters, such as: pH, protein content (with Folin-Ciocalteu reagent) and pectinmethylesterase activities (PME) by the titrimetric method, were analyzed from the juice of kiwi, mango, avocado and persimmon fruits. From each type of fruit, three samples were analyzed. The results were statistically evaluated. Descriptive statistical parameters revealed very large variability of PME activity in persimmon juice (CV%=50). The t test highlighted that: pH values differed very significantly between fruits juices, protein content was significantly higher in kiwi juice (0.779 mg%) and persimmon (0.485 mg%), compared to other juices (t varied between 14.246*** - 179.365***; p<0.001). Mango and avocado juices had lower and similar protein content (0.317 mg% and 0.324 mg%, t=0.281 ns). The PME activity (ɳEqv carboxyl/gs) had the following values: 29.993 in kiwi, 16.660 in mango, 56.660 in avocado and 106.650 in persimmon juice. The variance analysis (ANOVA) of the PME activity revealed, with a probability of error less than 5%, that there were real differences between at least two of the fruit juices. The post hoc Tukey HSD test revealed that PME activity in persimmon juice was significantly higher than the PME activity in kiwi and mango juices (p=0.035, respectively p=0.015). It can be said that the mango and kiwi fruits, analyzed in our experiment, seemed to be in a more advanced ripening phase, compared to avocado and persimmon fruits.